Myxomavirus serpin alters macrophage function and prevents diffuse alveolar hemorrhage in pristane-induced lupus - Zhuang, Haoyang (Clinical immunology (Orlando, Fla.), 2021)
Copyright © 2021. Published by Elsevier Inc.